2022
DOI: 10.3390/ijerph19084706
|View full text |Cite
|
Sign up to set email alerts
|

Is Active Moss Biomonitoring Comparable to Air Filter Standard Sampling?

Abstract: Recently, significant attention has been paid to air quality awareness and its impact on human health, especially in urban agglomerations. Many types of dust samplers for air quality monitoring are used by governmental environmental monitoring agencies. However, these techniques are associated with high costs; as a consequence, biological methods such as active moss biomonitoring are being developed. The main disadvantages of such techniques are the lack of standardization of the preparation procedures and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Notably, the absorption of pollution by moss was assumed to linearly occur. However, other research [9] has suggested that the absorption of polluting substances by moss generally follows a non-linear pattern. The model calculated the spread of pollution, assuming that pollution levels would be averaged out in neighboring subregions defined by a hexagonal grid.…”
Section: Limitations and Future Research Linesmentioning
confidence: 91%
See 2 more Smart Citations
“…Notably, the absorption of pollution by moss was assumed to linearly occur. However, other research [9] has suggested that the absorption of polluting substances by moss generally follows a non-linear pattern. The model calculated the spread of pollution, assuming that pollution levels would be averaged out in neighboring subregions defined by a hexagonal grid.…”
Section: Limitations and Future Research Linesmentioning
confidence: 91%
“…Moss is an intriguing plant known for its capacity to achieve a high level of air purification, particularly under conditions of stable temperature and humidity. Previous research [9] outlined a moss biomonitoring method utilizing three moss types: Pleurozium schreberi, Sphagnum fallax, and Dicranum polysetum. This method involved measuring the concentration of analytes (Mn, Fe, Cu, Zn, Cd, Hg, and Pb) accumulated within the total suspended particulate matter collected from dust collector filters in Opole (Opole Voivodeship, Poland).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation